Pendampingan Guru Ngaji melalui Pembekalan Metode Tadrijiyan dalam Menghafal Al Quran di TPQ Masjid Darussalam Desa Prajegan Sukorejo Ponorogo - Hartono Hartono; Asaduddin Luqman; Tamrin Fathoni (Social Science Academic, 2025)
The Tadrijiyan method, rooted in gradual and repetitive learning, is recognized as an effective approach for Quran memorization. However, challenges remain in implementing this method at TPQ Masjid Darussalam in Prajegan Village, Sukorejo District. This study aims to develop and implement a training program for Quran teachers using the Tadrijiyan method to enhance their teaching effectiveness. The research employed Participatory Action Research (PAR), involving stages of problem identification, action planning, implementation, observation, and reflection. Data were collected through participatory observation, in-depth interviews, and documentation, followed by qualitative descriptive analysis. The findings indicate that the Tadrijiyan method significantly improved teachers' ability to guide Quran memorization, resulting in increased student motivation and better memorization outcomes. Teachers reported greater confidence in applying structured and systematic teaching techniques. The study concludes that the Tadrijiyan method effectively supports Quranic education at TPQ Masjid Darussalam and recommends its broader application in similar educational settings. Future studies should explore its implementation in diverse contexts and consider developing more comprehensive teaching modules.